Ultrasound differential diagnosis of different forms of stomatogenic maxillary sinusitis - S. D. Varzhapetyan (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Objective: to improve the efficiency of diagnosis of various forms of stomatogenic maxillary sinusitis.